2014
DOI: 10.18553/jmcp.2014.20.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Adherence Measures and Resource Use in SSRI/SNRI-Treated Patients with Depression Using Second-Generation Antipsychotics or L-Methylfolate as Adjunctive Therapy

Abstract: BACKGROUND: Antidepressant monotherapy is effective in achieving treatment remission in only approximately one third of patients with depression, and even switching to a second antidepressant brings the cumulative remission rate to only 50%-55%. This has led to an interest in augmentation therapy for the management of treatment-resistant depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…To ensure ADs were being used to treat a new diagnosis of MDD, patients with claims for certain conditions were excluded from the dataset if they occurred within 6 months before to 12 months after the IDD (Appendix 2). These include schizophrenic disorder (ICD-9 code: 295), bipolar disorder (296.0–296.1 and 296.4–296.9), other psychosis-related disorders, paranoid states (297), other mood disorders (293.83 and 301.13), drug-induced depression (292.84), depressive-type psychosis (298), Alzheimer’s disease (331), Parkinson’s disease (332), and dementia (290) [12, 14, 22]. In addition, patients who had a claim for pregnancy (630–679) were excluded from the dataset because of the effect pregnancy may have on discontinuation of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure ADs were being used to treat a new diagnosis of MDD, patients with claims for certain conditions were excluded from the dataset if they occurred within 6 months before to 12 months after the IDD (Appendix 2). These include schizophrenic disorder (ICD-9 code: 295), bipolar disorder (296.0–296.1 and 296.4–296.9), other psychosis-related disorders, paranoid states (297), other mood disorders (293.83 and 301.13), drug-induced depression (292.84), depressive-type psychosis (298), Alzheimer’s disease (331), Parkinson’s disease (332), and dementia (290) [12, 14, 22]. In addition, patients who had a claim for pregnancy (630–679) were excluded from the dataset because of the effect pregnancy may have on discontinuation of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…19 Several studies have demonstrated l-methylfolate as an effective augmentation strategy with SSRI/SNRIs. 99,100 Comparative assessment of adherence measures and resource use in SSRI/SNRI-treated patients with depression using second-generation antipsychotics or L-methylfolate as adjunctive therapy http://www.ncbi.nlm.nih.gov/pubmed/24372461 101 "Patients who augmented SSRI/SNRI therapy with second-generation atypical antipsychotics (SGA) or Lmethylfolate achieved modified application of the HEDIS (mHEDIS) acute medication management (AMM) acute phase and continuation phase adherence scores of 69%-79% and 50%-62%, respectively. These modified scores exceeded the 2012 national median benchmarks for unmodified HEDIS AMM measures for commercial health plans.…”
Section: Treatment Of Cognitive Deficits Associated With Schizophrenimentioning
confidence: 99%
“…SSRI). The use of second-generation antipsychotics as adjuvants to SSRIs has been investigated and approved for clinical use to treat depression, particularly treatment-resistant depression, late-life depression and co-morbid MDD and alcohol dependence [75][76][77]. The combination of an SSRI and an antipsychotic has been proven to be more effective than a SSRI alone in patients with MDD [78].…”
Section: Effects Of Novel Strategiesmentioning
confidence: 99%